Co-injection with inactivated Enterococcus faecium and inactivated H1N1 influenza virus intravenously strengthen the protection of H1N1 influenza virus infections in mice - Li, Jinlian; Ren, Yifei; Xue, Mei; Shao, Di; Zhuang, Lili; Shen, Zhengyang; Tang, Zitong; Cui, Yuan; Shi, Youfei (Frontiers in Microbiology, 2025)
Influenza viruses pose a significant threat to human and animal health globally. Vaccine immunization is an effective strategy for preventing disease, reducing morbidity and economic losses, and enhancing quality of life. Enterococcus faecium is a Gram-positive, facultative anaerobic, lactic acid-producing bacterium that resides as a commensal in the gastrointestinal tract of animals and serves as a probiotic. This study investigated the effects of intravenous and intramuscular administration of inactivated E. faecium and inactivated influenza A H1N1 (PR8) virus on body weight, lung histopathology, HI antibody titers, immune cell composition in the spleen, and cytokine expression and viral load in the lungs of experimental mice following challenge. The results demonstrated that intravenous co-administration of inactivated E. faecium and inactivated H1N1 significantly mitigated weight loss and was associated with increased proportions of B cells, CD8+ T cells, and macrophages in the mouse spleen compared to other groups. Histopathological analysis revealed enhanced vascular-centered immune responses in the lungs of mice co-administered with inactivated E. faecium and inactivated H1N1. These findings suggest that co-administration of inactivated E. faecium and H1N1 virus enhances protection against H1N1 infection in mice, potentially improving vaccine efficacy.